2017
DOI: 10.1038/s41598-017-12862-x
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein impairs ferritinophagy in the retinal pigment epithelium: Implications for retinal iron dyshomeostasis in Parkinson’s disease

Abstract: Retinal degeneration is prominent in Parkinson’s disease (PD), a neuromotor disorder associated with aggregation of α-synuclein (α-syn) in the substantia-nigra (SN). Although α-syn is expressed in the neuroretina, absence of prominent aggregates suggests altered function as the likely cause of retinal pathology. We demonstrate that α-syn impairs ferritinophagy, resulting in the accumulation of iron-rich ferritin in the outer retina in-vivo and retinal-pigment-epithelial (RPE) cells in-vitro. Over-expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Proteins transferred to a PVDF membrane were probed with specific antibodies and developed by chemiluminescence as described (Baksi and Singh, 2017). Quantification of protein bands was performed by densitometry using UN-SCANT-IT (version6.1) software (Silk Scientific) and represented graphically.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins transferred to a PVDF membrane were probed with specific antibodies and developed by chemiluminescence as described (Baksi and Singh, 2017). Quantification of protein bands was performed by densitometry using UN-SCANT-IT (version6.1) software (Silk Scientific) and represented graphically.…”
Section: Methodsmentioning
confidence: 99%
“…As long-lived proteins, including ferritin, are degraded in the lysosome, rescue of lysosomal function by Synucleozid may account, in part, for reduction of ferritin levels. In support of this notion, a study in α-synuclein −/− mice showed that α-synuclein impaired ferritinophagy and conversely that elimination of α-synuclein reduced ferritin levels (35).…”
Section: Resultsmentioning
confidence: 93%
“…Ferritinophagy plays an important role in some physiological processes such as erythropoiesis . When ferritinophagy is deregulated, the abnormal iron balance leads to oxidative stress and pathological changes including neurodegenerative diseases …”
Section: Ferritinophagy Induction By Artesunatementioning
confidence: 99%
“…133 When ferritinophagy is deregulated, the abnormal iron balance leads to oxidative stress and pathological changes 134 including neurodegenerative diseases. 135 Yang et al 63 reported that, in human cervical cancer, ART accumulates in cellular lysosomes and decreases the levels of ferritin through the activation of lysosomes instead of proteasomes (Figure 4). In the presence of the autophagy inhibitors CQ or bafilomycin, ART-induced ferritin degradation is completely blocked, indicating the existence of ferritinophagy.…”
Section: Ferritinophagy Induction By Artesunatementioning
confidence: 99%